Fundamentals of advanced accounting - Hoyle, Joe Ben; Schaefer, Thomas F.; Doupnik, Timothy S. (New York : McGraw-Hill Education, 2020)
"Overall-this edition of the text provides relevant and up-to-date accounting standards references to the Financial Accounting Standards Board (FASB) Accounting Standards Codification® (ASC)"--
Revised edition of the authors' Fundamentals of advanced accounting, [2018]
Includes index.
Ages 18+
Keywords: Accounting